Brand Value : Nexus with Profitability and Value Relevance — Indian Evidence - Ramesh, Latha (Prabandhan: Indian Journal of Management, 2022)
The paper studied the association between brand value and financial profitability metrics, value relevance, and excess market returns. The study used the dollar value data of BrandZ ‘Top Indian Brands’ as the proxy for brand value and used 221 firm years for a sample of 72 companies that owned the top brands for 5 years, from 2014 – 2018. The study deployed the fixed effects model to find the association between profitability, firm value, and brand value and the Fama – French four-factor model for the risk-return performance of high-brand value stocks. The findings indicated a strong association between the brand values of firms and profitability and firm value. The portfolio returns of high-brand value companies produced higher risk-adjusted returns over market returns offered by BSE 100 stocks. This is India’s first and most comprehensive study to provide empirical evidence on the nexus between brand value, profitability, and value relevance. The results gave a concrete conclusion that building brand value offers both customer satisfaction as well as shareholder value creation.